The implementation of effective teamwork in rural schools : the case of Luthuli Park Combined School - Mamabolo, Patrick Ramahlape (My University, 2016)
Some teamwork in learning are effective and others are not. There are a number of factors or attributes that are needed for the implementation of an effective teamwork. The aim of this study was to describe how learners grapple with the use of teamwork for effective teaching and learning in impoverished rural secondary schools. A case study research design was adopted to gather data. The study was conducted in Luthuli Park Combined School in Limpopo Province. The research participants were learners from this school. The study was oriented in an interpretive paradigm following mixed methods approach. Multiple methods of data collection were used. First, data were collected through individual interviews with learners. Second, questionnaires were distributed to the learners to gather quantitative data. Finally, an observation method was used to collect data such as time management by learners, their behavioural patterns and the way they team themselves in the classroom. The study found that the majority of the learners did not listen to suggestions from their team members; they lacked listening skills. In particular, the study indicated that 46% of the learners listened to each other’s suggestions while 54% reported that they did not listen to each other’s suggestions. The main finding of the study is that teamwork among learners is still problematic. The conditions within the classroom prohibited the effectiveness of teamwork. For example, lack of textbooks, physical resources (chairs, desks, data projectors, et cetera). The findings of the study reveal an indecisive and autocratic mind-set among learners regarding the involvement of teamwork. The study recommends that the implementation of effective teamwork will play a vital role in improving performance of the learners.
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2016
Keywords: Team work; Effective teaching and learning; Education -- Study and teaching; Team learning approach in education; Group work in education -- South Africa -- Limpopo